Fundamentos do direito do desporto na atmosfera econômica e empresarial brasileira - Bastos, Guilherme Augusto Caputo (2022)
This doctoral thesis aims to identify and problematize the specificities pertinent to the domain reserved for sport, focusing on aspects related to its origin and the perspective of its evolution, as a fundamental right enshrined in the Federal Constitution, in the Brazilian socioeconomic context, notably in view of its cultural relevance and the legal repercussion of the various relationships that are formed by virtue of a sporting activity. It seeks to explore the link between the concept of Creative Economy and sport in Brazil and in the world. It proposes to give Sports Law treatment consistent with its condition of autonomy and independence, although it intends to establish a subsidiary connection with other branches of the national legal system, especially Labor Law. Proceed to the exam and proposes eminently legal solutions in terms of established demands in the sports scene, such as those referring to State intervention, the formalities of the special sports employment contract, moral damage, doping, transsexuality and effectiveness of international standards in Brazilian sport.